PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN PADA APLIKASI OJEK ONLINE INDRIVE DI SURABAYA - Nanda Achmida; Winaika Irawati (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
The online transportation industry is facing increasingly intense competition in Surabaya. This has impacted InDrive's customer loyalty. Several issues frequently complained about by customers include driver delays during pick-up and drop-off, inaccurate navigation systems, and unprofessional driver behavior. Furthermore, the pricing mechanism for negotiations creates inconsistent price perceptions among customers. This presents a challenge for the company in maintaining user loyalty. This study aims to examine the influence of service quality and price perception on customer loyalty among InDrive online motorcycle taxi (ojek) users in Surabaya, both partially and simultaneously. Using a quantitative approach with an explanatory research approach, the data collection method involved distributing questionnaires to 100 active InDrive users in the Surabaya area. The data analysis techniques include classical assumption tests, multiple linear regression analysis, t-test hypothesis testing (looking at partial effects), and F-tests (looking at simultaneous effects). The results of the analysis show that partially, service quality (X1) and price perception (X2) have a positive and significant influence on customer loyalty (Y). Simultaneously, both variables are proven to have a positive and significant influence on customer loyalty. The coefficient of determination (R2) of 0.480, or 48%, indicates that variations in customer loyalty can be explained by service quality and price perception, while the remaining 52% is influenced by other factors outside the research model. Therefore, it can be concluded that service quality and price perception are important factors in increasing customer loyalty at InDrive in Surabaya.